2004
DOI: 10.4049/jimmunol.172.12.7476
|View full text |Cite
|
Sign up to set email alerts
|

MHC-Restricted Ig V Region-Driven T-B Lymphocyte Collaboration: B Cell Receptor Ligation Facilitates Switch to IgG Production

Abstract: B cells spontaneously process their endogenous Ig and present V region peptides on their MHC class II molecules. We have here investigated whether B cells collaborate with V region-specific CD4+ T cells in vivo. By use of paired Ig L chain-transgenic and TCR-transgenic mice and cell transfer into normal hosts, we demonstrate that B cell presentation of a VL region peptide to CD4+ T cells results in germinal centers, plasma cells, and Ab secretion. Because the transgenic B cells have a fixed L chain but polyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 65 publications
2
77
0
Order By: Relevance
“…For these reasons, T cells that recognize rare Id-peptides, arising as a consequence of somatic genetic events unique to each B cell, may play a special importance in Id-driven T-B collaboration, immunosurveillance of B-cell malignancies, and Id-vaccination. development of autoimmune disease [16][17][18][19] and even B lymphomas [20]. These findings were corroborated by detection of Id-specific T cells in mouse models of SLE [14,15] and human autoimmune disease like SLE [21,22], rheumatoid arthritis [23] and multiple sclerosis [24].…”
Section: Introductionsupporting
confidence: 59%
“…For these reasons, T cells that recognize rare Id-peptides, arising as a consequence of somatic genetic events unique to each B cell, may play a special importance in Id-driven T-B collaboration, immunosurveillance of B-cell malignancies, and Id-vaccination. development of autoimmune disease [16][17][18][19] and even B lymphomas [20]. These findings were corroborated by detection of Id-specific T cells in mouse models of SLE [14,15] and human autoimmune disease like SLE [21,22], rheumatoid arthritis [23] and multiple sclerosis [24].…”
Section: Introductionsupporting
confidence: 59%
“…Our previous studies demonstrated that B cell Ag presentation (of Id) in itself is insufficient for the generation of the germinal center reaction: B cells also require BCR ligands for the response (31). Contingent upon the presence of DNA, naive anti-dsDNA B cells with one or two CDR3 arginines could be helped by the low-frequency Id-specific Th cells in the mice to isotype switch to IgG and accumulate one or two additional CDR3 arginines by somatic hypermutation.…”
Section: Discussionmentioning
confidence: 99%
“…Diluted serum samples were analyzed for the presence of anti-dsDNA Abs or other autoantibodies, as previously described (32,33) Cells were fixed with paraformaldehyde before acquisition. DTG splenocytes or BALB/c controls were cultured with Th2 cells from Id-specific TCR-TG SCID mice, as described (31). BrdU was added on day 3, and cells were stained on day 5 with the BrdU-APC Staining Kit (BD), including surface stains for B220, CD4, and CD19.…”
Section: Autoantibody Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…8 -12 Conversely, Id ϩ B cells can be helped by Id-specific CD4 ϩ T cells and differentiate into antibody 10,13 and autoantibody [13][14][15] secreting B cells. Such findings have paved the way for the concept of Id-driven T-B collaboration, as first suggested by our group.…”
mentioning
confidence: 99%